Dampak Riba Terhadap Sosial Ekonomi Pedagang Pasar; Studi Pedagang Pasar Semuli Raya Lampung Utara - Aye Sudarto (Universitas Islam Lamongan, 2021)
Abstract: In economic activity, capital is the most crucial thing. Obtaining that basic financial factor can be done independently or through submitting loans from other parties (investors). Until now, the lower class still have difficulty dealing with financial institutions, related to certain requirements. Consequently, they choose the easiest way, without any complicated pre-requirements, commonly known as loan sharks. This research is qualitative field research using descriptive analysis. The findings reveal that the reason these traders make capital submissions to moneylenders is because the process of borrowing money is fast and easy. They do not have to have valuables as collateral. In addition, the amount of money is moderately small. Relying on trust, they can immediately receive the loans. The rent-seeking among the community, practically, has a lot of negative impacts on the community's economy. The rent-seeking carried out in Semuli Raya, Abung Semuli Subdistrict, has caused the people's economy, especially the market traders, to be very disturbed both for their daily needs and even on the education of their children. Keywords: usury; market trader; money lender